Turbulent Afghanistan A Critical Analysis of the US Politics of Confinement and the Rise of the Taliban (Taylor & Francis, 2024)
This book explores the what, the why, and the how of the Taliban takeover of Afghanistan almost 20 years after their removal from power. It examines how the U.S. discourses on War on Terror and state-building in Afghanistan have taken shape, became dominant over the past two decades, and to delineate their consequences. Also, it highlights how both discourses are representative of wider depoliticization of the society and eventually paved the way for the illiberal, oppressive politics of confinement and necropolitics. The volume will be of great interest to scholars and researchers of politics and international relations, U.S. foreign policy, peace and conflict studies, area studies, especially West Asian and South Asian studies.
English
Keywords: Afghanistan,Taliban,US War on Terror,Rise of the Taliban,US Politics of Confinement,Afghan Government,State Building Discourse,Post-2001 Afghanistan,Vice Versa,NATO Troop,Al Qaeda,WoT,Afghan Society,PDPA,Taliban Rule,NSS,Bin Laden,Osama Bin Laden,International State Building,Conceptualizing State Failure,Mujahidin Groups,Afghan Security Forces,ANSF,Boko Haram,Dead Men,Afghan People,Bagram Air Base,Kandahar Province,CIA Team,Alp; thema EDItEUR::G Reference, Information and Interdisciplinary subjects::GT Interdisciplinary studies::GTM Regional / International studies; thema EDItEUR::J Society and Social Sciences::JB Society and culture: general; thema EDItEUR::J Society and Social Sciences::JP Politics and government::JPS International relations; thema EDItEUR::J Society and Social Sciences::JW Warfare and defence